Impact of Tourism Destination Strategy on Its Competitiveness - Dunja Demirović; Radovan Pejanović; Otilija Sedlak; Kristina Košić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 8-9 September 2016, 2016)
The aim of this paper is to explore how destination strategy – marketing, employees, policy of planning and destination development, management of service quality and management of environmental protection - affects competitiveness of rural tourism destinations in Vojvodina (Serbia) and Hungary. Tourism experts in Vojvodina (136) and Hungary (138) were asked to evaluate the current condition of all 24 attributes which affect the competitiveness of rural tourism destinations. Likert scale of five marks was used in order to determine the effect of the strategies on the competitiveness of Vojvodina/Hungary as a rural tourism destination. Authors concluded that a large number of tourist resources and attractions are irreplaceable, and the purpose of formulating and implementing strategies must be to ensure that the use of resource ensure their long-term sustainability. Such a development strategies are processes or activities that correspond to the tourist attractions and resources of destinations, and on the other hand, are aligned with the external environment. Destination competitiveness can be increased by using a strategy of constant innovation and continuous change. In order to be competitive, destination should offer flexible, segmented and customized products. The main methods of developing flexibility for the competitiveness of tourist destinations rely on the organization, management, marketing, distribution and other forms of interactions and relationships between tourism suppliers.
Keywords: Q13; Z32; 330; tourism destination; strategy; competitiveness; management; Vojvodina (Serbia); Hungary